Transcriptional Regulation of CYP2D6 by Nrf2 and Its Implications in Breast Cancer Therapy: Bioinformatics and Experimental Evidence - Ferbian Milas Siswanto; Maria Dara Novi Handayani; Lonah Lonah; Rita Dewi; Zita Arieselia; Linawati Hananta; Putu Suwarastra Andarisuta (Indonesian Biomedical Journal)
BACKGROUND: Tamoxifen (TAM) resistance in patient with breast cancer is the leading cause of mortality among women globally. Cytochrome P450 2D6 (CYP2D6) is involved in the metabolism of TAM, and recently NF-E2-related factor 2 (Nrf2) has recently been found as its regulator. However, the impact of Nrf2-mediated CYP2D6 regulation in the context of breast cancer and TAM resistance are currently unknown. Therefore, this study was conducted to examine the role of CYP2D6 and Nrf2 in breast cancer prognosis.